Regional differences in the effects of healthy aging on depressive symptoms: a Korean longitudinal study of aging (2006–2020) - Kang, Soo Jin; Hwang, Jinseub; Kim, Dohyang; Kim, Bongjeong (Frontiers in Public Health, 2024)
Background: Depression is a widely prevalent, often recurrent condition. To analyze the regional differences in depressive symptoms over time, we investigated urban-rural differences in change in depression over time in South Korea and the association between healthy aging and depressive symptoms among middle-aged and older adults. Methods: Data collected in the Korean Longitudinal Study of Aging, from 2006 to 2020, of adult participants aged ≥ 45 years without depressive symptoms were analyzed. Healthy aging was defined under five principal components: absence of chronic disease, good physical function, normal cognitive function, active social engagement, and good psychological adaptation. Depressive symptoms were measured using the short version of the Center for Epidemiologic Studies Depression Scale. Using the Andersen−Gill model for recurrent time-to-event, we examined the effect of healthy aging on depressive symptoms, with a subgroup analysis based on the residential area. Results: Of the 7,708 participants, 78.2% lived in urban areas and 39.4% achieved healthy aging. In 2008, rural residents had a higher incidence of depressive symptoms (rural 11.8%; urban 8.9%); however, after 2016, the depressive symptoms of urban residents gradually increased (rural 6.4%; urban 12.1%). Unhealthy aging (adjusted hazard ratio=3.04, 95% confidence interval: 2.72−3.39) and urban residence (adjusted hazard ratio=1.15, 95% confidence interval: 1.06−1.24) were risk factors for depressive symptoms. The subgroup analysis revealed that individuals who did not achieve healthy aging had an increased risk of depressive symptoms, regardless of their residential area (hazard ratio [95% confidence interval]: urban, 3.13 [2.75-3.55]; rural 2.59 [2. 05-3.28]). Conclusion: As urbanization accelerates, urban residents have a higher risk of depressive symptoms than rural residents. Healthy aging is an essential factor in reducing depressive symptoms. To achieve healthy aging, appropriate interventions and policies that target the middle-aged adults and gradually extend to older adults are needed, considering individual and regional factors.